APLIKASI ZAT PENGATUR TUMBUH DALAM INDUKSI PEMBUNGAAN ANGGREK BULAN (Phalaenopsis sp.) - Hayuning Martha L.A; Euis Elih Nurlaelih; Tatik Wardiyati (Universitas Tribhuwana Tunggadewi, 2011)
Phalaenopsis amabilis is one orchid flower have a higher economic value commercial flowers.The aims of this study was to determine Plant Growth Regulators (PGR) in inducing flowering Phalaenopsis sp. Randomized Complete Block Design was used with three replications. Non destructive observations were made such as number of leaves and leaf area, initiation of flower spike, length of flower stalk, flower initiation, length of panicle, number of flowers bud, Number of flowers bloom, flower diameter, and percentage of flowering plants. The results showed that there is interaction between kinds of PGR and types of flowers on vegetative growth. The best applications PGR is BA 200 ppm inducing flowering 100% and accelerate the time of flower initiation 23 days after treatment. Aplication 100 ppm Paclobutrazol promote 50% in the percentage of flowering and 100 ppm GA3 promote 33.3% in the percentage . Effect of Paclobutrazol on Phalaenopisi only for type of purple flower